Second-order optimality conditions for singular extremals in optimal control problems with equality endpoint constraints. (July 2017) - Arutyunov, A.V.; Shvartsman, I.A.; Zhukovskaya, Z.T.
Abstract: In this paper we use the method of finite-dimensional approximations to derive the second-order necessary optimality conditions for singular Pontryagin local minimizers in optimal control problems with equality endpoint constraints.